Mediterranean diet recommended not only in cardiovascular diseases - Chudzińska, Małgorzata; Wołowiec, Łukasz; Zukow, Walery; Sinkiewicz, Władysław (Journal of Education, Health and Sport, 2017)
The Mediterranean diet is characterized by high consumption of vegetables, fruits, cereals, nuts, olive oil (rich in monounsaturated fatty acids), fish (rich in Omega - 3 fatty acids) and moderate consumption of dry red wine. The positive impact of the diet on life expectancy and cardiovascular disease has been widely discussed, but further studies prove that it is also beneficial in supporting treatment of other civilization diseases such as diabetes, obesity, cancer, infertility and neurodegenerative or autoimmune diseases. Although certain studies on the effects of the Mediterranean diet still require further action, they undoubtedly give hope that the proper nutrition can have a significant impact on the prevention and treatment of civilization diseases.